Performance of dryland rice cultivars in function of soil preparation systems and sprinkler irrigation - Arf, Orivaldo; Rodrigues, Ricardo Antonio Ferreira; Crusciol, Marco Eustáquio Costa; Crusciol, Carlos Alexandre Costa (Pesquisa Agropecuaria Brasileira, 2001)
The present paper had the objective to evaluate the performance of dryland rice cultivars in different soil preparation systems and water deep applied through sprinkler, in Selvíria County, MS, Brazil. Treatments consisted of combination of three rice cultivars (IAC 201, Carajás and Guarani), three soil preparation systems (moldboard plow + disking, chisel + disking, and disk harrow + disking) and three levels of irrigation by sprinkler (zero and two water deeps), with four replications. The use of irrigation by sprinkler reduced the number of days to full flowering and the cycle of crop. The Carajás cultivar presented the largest grain production and practically absence of lodging in comparison to IAC 201 and Guarani. Soil preparation with moldboard plow and chisel provided the largest grain production in relation to other preparation systems, in moisture stress condition. The two water deeps increased the grain production in 113% and 177%, respectively, in the year with moisture stress.
Keywords: mouldboard ploughs; harrows; disks; soil water retention; irrigation rates